PERFORMA KELEMBAGAAN PENGELOLAAN KAWASAN KONSERVASI BERBASIS MASYARAKAT - Subhan Subhan; Sjamsu Alam Lawelle (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
Starting from the urgency to protect nearshore areas from destructive fishing, a group of people in Saponda Island set up a local  marine sanctuary, known as Marine Manage Area. The initiation to establish marine manage area has been commenced since 2004. Marine Manage Area is an institution that was set up by local community in which the participation of the community during the establishment was involved such as village administration and non government organization. The performance of the sanctuary’s institution are characterized by three primary components: jurisdiction boundary, property right, and rule of representation. The aim of this paper was to provide information on the performance in managing the institution of Marine Manage Area located in Saponda Island.               Keywords: Institution, Manage Sea Region, Saponda